Franklin Evans, or The Inebriate : A Tale of the Times - Whitman, Walt, 1819-1892 (Book collections on Project MUSE., 2007)
Less a novel than a prohibition tract in fiction, its clich-even-then story is that of an innocent from Whitman's native Long Island and his corruption by the music halls and taverns of New York City. It ends with the hero sagely advising that every young man should marry as soon as possible, and have a home of his own.